The role of TNF-α in a murine model of Kawasaki disease arteritis induced with a Candida albicans cell wall polysaccharide. Issue 1 (January 2014) - Oharaseki, Toshiaki; Yokouchi, Yuki; Yamada, Hitomi; Mamada, Hiroshi; Muto, Satoshi; Sadamoto, Kiyomi; Miura, Noriko; Ohno, Naohito; Saji, Tsutomu; Naoe, Shiro; Takahashi, Kei
Abstract: Objectives Various inflammatory cytokines, including tumor necrosis factor-α (TNF-α), have been reported to play roles in Kawasaki disease (KD). Recently, anti-TNF-α therapy was reported to show efficacy in patients who do not respond to high-dose intravenous immunoglobulin therapy. However, there are many gaps in our understanding of the role that TNF-α plays in the development of KD arteritis as well as whether anti-TNF-α therapy causes any histological changes in the arteritis. Accordingly, the present histopathological study was carried out to elucidate the inhibitory effect of anti-TNF-α therapy on vasculitis as well as the role of TNF-α in the development of vasculitis in a murine model of KD vasculitis. Methods We used two anti-TNF-α drugs (etanercept and infliximab) to treat a Candida albicans -induced murine model of KD vasculitis. We investigated the histopathological changes in terms of the incidence of vasculitis, the scope of lesions and the degree of inflammation. Results Administration of etanercept to the mice reduced not only the incidence of vasculitis but also the scope of lesions and the degree of inflammation. Conclusion Based on the histological findings, TNF-α is deeply involved in the development of vasculitis.